Do electoral rules matter? Explaining national differences in women's representation in the European Parliament. (December 2014) - Fortin-Rittberger, Jessica; Rittberger, Berthold
The European Parliament (EP) has one of the highest proportions of women in its ranks, with over a third in 2009. Although previous research has pointed to the use of proportional representation (PR) in European elections as 'friendlier' to women, few have looked at differences in the types of PR rules in use in each country. In this article, we argue that the conventional wisdom according to which institutional design—the choice of electoral rules—should shape the composition of the EP does not hold, and suggest that the well-documented empirical connection between electoral rules and descriptive representation might in fact be an endogenous rather than a causal relationship.